Implementasi Website Sistem Administrasi Dinas Pendidikan (Siadik) Di Dinas Pendidikan Provinsi Jambi - Husna Tumanggor, Nurul; Nofi Nurman (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to analyze the implementation of the Education Office Administration System Website (SIADIK) at the Jambi Provincial Education Office as a form of E-Government implementation in improving the effectiveness of public service administration. SIADIK is a digital-based administrative platform developed by the Educational Information and Communication Technology Center (BTIKP) since the end of 2022, with the goal of accelerating correspondence processes, facilitating letter disposition, enhancing administrative transparency, and supporting digital archiving. This study employs a descriptive qualitative method, collecting data through observation, in-depth interviews with 15 informants, and documentation. Data analysis was conducted using George C. Edward III's policy implementation model, encompassing four key variables: communication, resources, disposition, and bureaucratic structure. The findings reveal that SIADIK implementation has been carried out gradually and has yielded positive impacts, including a significant acceleration in letter processing with an overall time efficiency of 72.3%, improved transparency in disposition workflows, and enhanced bureaucratic work efficiency. However, implementation still faces challenges such as limited ongoing socialization, technological infrastructure gaps in peripheral schools, and the absence of specific Standard Operating Procedures (SOPs) to formally regulate system usage. Therefore, increased socialization and training, strengthened information technology infrastructure, and the formulation of dedicated SOPs are needed to support the sustainability and optimization of SIADIK implementation.